We're going on a picnic! - Hutchins, Pat, 1942- ([New York] : Greenwillow Books, 2002)
Hen, Duck, and Goose go on a picnic but have trouble deciding where to stop and eat.
2.9
K-3
K-3
Wilson's Children
School Library Journal
Publisher's Weekly
Keywords: Picnicking -- Fiction; Chickens -- Fiction; Ducks -- Fiction; Geese -- Fiction; Picnicking -- Fiction; Chickens -- Fiction; Ducks -- Fiction; Geese -- Fiction